Comparison of Antibacterial Efficacy of Locally Produced Alcohol Based Hand Sanitizer and Commonly Available Commercial Hand Sanitizer Used in Healthcare Facilities in Uganda - Tusabe, Fred; Kasuswa, Sophia; Ssegawa, Alex; Busiinge, Emmanuel; Lusheda, Tom; Ampaire, Lucas (Open Access Library Journal, 2020)
Use of hand sanitizers has become a cornerstone in clinical practice for the prevention of disease transmission between practitioners and patients. There are a number of hand sanitizers sold on the Ugandan market with labels on their packages that claim that the hand sanitizer can kill 99.999% of germs and also there are hospitals that embarked on the local production of alcohol based hand sanitizer whose efficacy data are not locally available. Objective: To evaluate antibacterial efficacy of locally produced alcohol based hand sanitizer and commonly available commercial hand sanitizer used in healthcare facilities in Uganda. Method: This was an in vitro experimental, laboratory-based study of two different brands of hand sanitizers commonly used in healthcare facilities in Uganda and these were compared to a reference standard 60% Isopropyl alcohol. Efficacy was evaluated using standard organisms of Klebsiella pneumoniae American Type Culture Collection (ATCC 13883), Escherichia coli (ATCC 25922), and S. aureus (ATCC 25923) as per prEN12054, a European standard method. The logarithmic and percentage reduction factors (RF) were assessed at baseline and after treatment. Results: Both hand sanitizers studied were able to reduce bacteria by more than 105-fold within 15 seconds. Efficacy was independent of the alcohol concentration in each brand (Saraya 70% and locally made 80% alcohol). Conclusion: All of the hand sanitizers assessed had efficacy that meets World Health Organization (WHO) and PrEN12054 standards. From this study we are in agreement with the use of the locally made hand sanitizer and Saraya. The two hand sanitizers had broad antibacterial spectrum. However, there is a need to evaluate efficacy and organoleptic properties using in vivo studies.
Keywords: Hand Sanitizer, Efficacy, Uganda, Antibacterial